Evaluating mathematics teachers’ usage of online tools to enhance learning performance of high school students - Salami, Olajumoke Olayemi; Spangenberg, Erica Dorethea (Institute of Advanced Engineering and Science, 2025)
The application of digital technologies to teach mathematics is increasing and how educators use these tools and their impact on the performance of students needs to be sufficiently researched. In this study, we explore middle school mathematics teachers’ utilization of Algebra Nation (AN), an online instructional resource, to supplement instruction and improve the performance of their mathematics students, particularly in algebra. A survey was conducted involving 596 teachers and a quasi-experimental trial. We examined the relationship between AN use and Algebra I end-of-course (EOC) exam performance. The findings showed that engagement in AN observed through student login, video watches, and professional teacher development is associated with improved student’s success rates in mathematics. This study also revealed that challenges such as digital disparity, data privacy issues, and professional teacher development were identified to impact the effective implementation of digital technologies in teaching mathematics. This study recommends that there should be systematic integration of web resources, combined with targeted teacher training to significantly enhance mathematics instruction. These conclusions inform future technology adoption and policymaking, with emphasis on equal access and systemic teacher support.